Relevansi Filsafat Progresivisme Dalam Pembelajaran Berdiferensiasi Pada Kurikulum Merdeka - Nuri Simarona; Taufan Untung Wibowo Silitonga; Agus Elpin; Warneri Warneri; Aunurrahman Aunurrahman (Journal on Education, 2024)
To encourage continued curriculum development, it is necessary to explore the relevance of the philosophy of progressivism and differentiated learning in the context of the Independent Curriculum. Therefore, this research was designed to answer these questions through literature exploration and provide insight into the principles of progressivism that can be applied in differentiated learning to achieve the goals of the Independent Curriculum. The method used in this research is descriptive qualitative research. This research was carried out by collecting data through literature studies, including books, journal articles, and relevant online sources. The data collected was then analyzed descriptively to understand the relevance of the philosophy of progressivism and differentiated learning in implementing the Merdeka Curriculum. The philosophy of progressivism and differentiated learning go hand in hand in implementing the Merdeka Curriculum in Indonesia. Both emphasize developing students' abilities through experience and independence. With this approach, students can learn according to their abilities and interests, and the teacher acts as a facilitator who adapts learning to the individual characteristics of students. The philosophy of progressivism and differentiated learning supports the Independent Curriculum in Indonesia, creating an inclusive and effective learning environment. Progressivism principles such as active and contextual learning are in line with differentiated learning strategies. Further research is needed to examine the implementation and effectiveness of this approach in the Merdeka Curriculum.